(untitled) (Journal of Comparative & International Higher Education, 2022)
Research on the international students mostly focuses on adjustment and acculturation issues rather than building and maintaining wellness of specific cultural groups of international students. This study used basic psychological needs involved in self-determination theory to investigate the relationship between autonomy, competence, and relatedness needs, self-determined way of functioning, and wellness of Turkish international students in the U.S. Data was collected before Covid-19 pandemic using a self-administered survey from 179 (71 females) Turkish international students with a mean age of 29.7 years. The results indicated that the perceived total wellness of Turkish international students was slightly low. The results of regression analyses revealed that autonomy, competence, and relatedness are positive and significant predictors of Turkish international students’ wellness. Furthermore, Turkish international students with a greater self-determined way of functioning report higher level of wellness. We recommend culture specific implications and further research to maintain international students’ wellness in their sojourn.